Flowsheets for the Validation of the Reference AmSEL System - Vanel Vincent; Wilden Andreas; Modolo Giuseppe; Geist Andreas; Montuir Marc (EPJ Web of Conferences)
Recycling americium (Am) from spent nuclear fuels is an important option considered for the future nuclear fuel cycle as americium is the main contributor to the long-term radiotoxicity and heat power of the ultimate waste. The AmSEL flowsheet aims at recovering and purifying americium from a PUREX raffinate. This separation can be achieved by co-extracting lanthanide(III) (Ln) and actinide(III) cations (Am(III) and Cm(III)) into an organic phase containing the TODGA extractant (N,N,N’,N’-tetraoctyl diglycolamide), and then stripping Am(III) selectively towards curium and lanthanides. The water-soluble ligand SO3-Ph-BTBP (6,6′-bis(5,6-dialkyl-1,2,4-triazin-3-yl)-2,2′-bipyridine) is used to selectively strip Am from the loaded organic phase. The objective of this work is to design a flowsheet for the Am stripping and Cm re-extraction steps to recover americium selectively from Cm and Ln, with TODGA as extractant and SO3-Ph-BTBP as complexing reagent. The test was implemented in August 2023 at FZ Jülich with trace amounts of americium and curium.